2009
DOI: 10.1080/13813450902736583
|View full text |Cite
|
Sign up to set email alerts
|

The role of the insulin-like growth factor 1 receptor axis in multiple myeloma

Abstract: Multiple myeloma remains a fatal B cell malignancy with severe clinical features such as anaemia and bone fractures, caused by the predominant localization of the myeloma cells in the bone marrow (BM). The MM cells first migrate towards the BM, followed by their clonal expansion and induction of angiogenesis and osteolysis. Insulin-like growth factor 1 or IGF-1 is a cytokine which plays a role in myeloma development. Besides serving as a growth and survival factor, it attracts the cells towards the BM, and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 65 publications
2
24
0
1
Order By: Relevance
“…Our analyses confirmed that, compared with UC-MSCs, both nBM-and MM-BM-MSCs produce higher amounts of pro-MM cytokines, namely IL-6, IL-15, IGF-1, MIP-1a, OPG, and RANTES [34][35][36][37][38]. These results appear in line with most studies reporting that BM-MSCs from MM patients mediate the formation of an intense marrow gradient of soluble [39,40] or exosome-incorporated cytokines with a biological impact on the survival of myeloma plasma cells [6].…”
Section: Discussionsupporting
confidence: 72%
“…Our analyses confirmed that, compared with UC-MSCs, both nBM-and MM-BM-MSCs produce higher amounts of pro-MM cytokines, namely IL-6, IL-15, IGF-1, MIP-1a, OPG, and RANTES [34][35][36][37][38]. These results appear in line with most studies reporting that BM-MSCs from MM patients mediate the formation of an intense marrow gradient of soluble [39,40] or exosome-incorporated cytokines with a biological impact on the survival of myeloma plasma cells [6].…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, Pim-2 overexpressed in MM cells in the MM bone marrow microenvironment appears to be an important therapeutic target. IGF-1 is another critical microenvironment-derived survival factor for MM cells, 14,15 and inhibition of the IGF-1/PI3K/Akt pathway by Akt or mammalian target of rapamycin inhibitors has drawn considerable attention as a new therapeutic modality against MM. 19,20 Because Pim-2 upregulation is largely independent of the PI3K/Akt pathway (Figure 3e), and because inhibition of Pim-2 and PI3K/Akt pathways cooperatively reduce MM cell survival (Figures 4b and e), Pim-2 should be targeted to improve anti-MM efficacy together with PI3K/Akt pathway inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…2 One of the most important growth factors involved in MM progression is insulin-like growth factor-1 (IGF-1). [3][4][5] This cytokine induces proliferation of both interleukin-6 (IL-6)-independent and -dependent cell lines, acts synergistically with IL-6, and protects MM cells from dexamethasone-induced apoptosis. 3 Moreover, IGF-1 also stimulates homing and production of angiogenic factors.…”
mentioning
confidence: 99%